Exogenous hydrogen sulphide sensitizes carbapenemase-producing Acinetobacter baumannii to gentamicin - Nicolas Helsens; Jacqueline Findlay; Maxime Bouvier; Patrice Nordmann (Journal of Global Antimicrobial Resistance)
Objective: Carbapenem-resistant Acinetobacter baumannii pose a major public health threat. These bacteria often display broad-spectrum antibiotic resistance, rendering them resistant to nearly all classes of antibiotics. Hydrogen sulphide (H2S), a compound naturally produced by many bacterial species, has been proposed to exert a protective effect against certain antibiotics. However, A. baumannii does not produced H2S. Methods: To investigate the effect of exogenous H2S on antibiotic resistance, several clinical isolates of carbapenemase-producing A. baumannii were cultured under various conditions, including the presence or absence of H2S and/or sub-inhibitory concentrations of gentamicin, azithromycin, ciprofloxacin, tetracycline, and meropenem. Bacterial growth was assessed at multiple time points to evaluate growth dynamics. Results: Exogenous H2S alone had a limited impact on bacterial growth. However, its addition reduced the minimum inhibitory concentration of gentamicin and sensitized the bacteria to sub-inhibitory concentrations of this antibiotic. Conclusions: This study highlights the potential of H2S as an antibiotic potentiator, suggesting that the use of this combination may be a promising strategy for treating pulmonary infections caused by A. baumannii or for preventing colonization on medical devices such as catheters.